Upaya Meningkatkan Minat Siswa – Siswi Terhadap Olahraga Kasti Dengan Model Pembelajaran Direct Intruction Di SMPN 1 Kalimanggis - Yosep Alpualik Sidik; Didi Muhtarom (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
This research aims to increase students' interest in the sport of rounders with the Direct Instruction learning model. This research will be carried out at SMPN 1 Kalimanggis with research subjects being class VIII students at SMPN 1 Kalimanggis for the 2023/2024 academic year, and the sample used is class VIII A. This research is quantitative research with the type of pre-experimental research (pre-experimental designs) used in this research being one-group pre test – post test design. The research instruments used were observation and questionnaires using a Likert scale. The questionnaire or questionnaire will later be distributed twice during the pre-test and post-test. Before the post-test, the researcher will carry out treatment to deepen the material on baseball for the students. After the pre-test - post-test is carried out, the researcher will carry out data processing to determine the students' interest in the sport of rounders.